“Sharia Maqasid-Oriented Economic Ethics (MS-EE) and the Behavioral Patterns of Vegetable Traders in Indonesian Traditional Markets”: Etika Ekonomi Berorientasi Maqasid Syariah (MS-EE) dan Pola Perilaku Pedagang Sayur di Pasar Tradisional Indonesia - harir, muharir; Roby Candra Yudha, Ana Toni; Saprida; Melis (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2025)
Traditional markets serve as centers of grassroots economic activities that reflect the dynamics of social, cultural, and economic interactions within local communities. This study employs a qualitative approach with a descriptive method, supported by in-depth interviews with respondents, and the findings are validated through a triangulation analysis model. The results indicate that vegetable traders in the Traditional Market of Tirto Sari Village, Banyuasin I District, South Sumatra Province, play a strategic role in fulfilling the community’s food needs and driving local economic activities. Their economic behavior is reflected in capital management, sales patterns, and the social interactions they build with consumers. Understanding these behaviors is essential for examining the economic rationality and social values that influence trading practices, while also contributing to the strengthening of microeconomic development based on local wisdom aligned with the principles of maqasid al-sharia.